DIFFICULTIES IN LEARNING FOREIGN LANGUAGES - Ibrohimov , Qobiljon; Jaloldinov , Islomiddin (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article discusses the main difficulties encountered in the process of learning foreign languages. In particular, problems related to vocabulary, grammar, pronunciation, and motivation are analyzed. Additionally, possible ways to overcome these challenges are briefly considered.